UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG SISWA SEKOLAH DASAR KELAS IV DENGAN METODE JARIMATIKA - Ulfasari Rafflesia; Idhia Sriliana; Pepi Novianti (DHARMA RAFLESIA, 2018)
Community service activity aims to introduce and teach counting method of finger (jarimatika) as an alternative method of counting to complete the multiplication operation on the fourth grade students at SD Negeri 79 Kota Bengkulu. Counting method can be used to improve student learning outcomes in completing multiplication operations. This method can provide visualization of counting process, cheer up the child, not burdening the memory of the brain, and the tool is always taken. In addition, this method will make learning activities more fun so that the students become eager in learning. Based on the results of the dedication activities undertaken, it can be concluded that this activity is able to provide knowledge and skills to students of Class IV SDN 79 Kota Bengkulu about jarimatika method. Almost all students are very enthusiastic and interested in following this guidance activity although this jarimatika method is relatively new to them. In addition, this activity can improve students learning motivation and improve students’ numeracy skills especially in multiplication operations. Keywords: Counting, Jarimatika, Mathematics